Acupuncture combined with biofeedback electrical stimulation for female stress urinary incontinence: a systematic review and meta-analysis - Liu, Hongji; Aikebai, Aizizha; Yuan, Qianer; Chen, Jie (Frontiers in Medicine, 2026)
IntroductionThis meta-analysis aimed to determine the clinical efficacy of acupuncture combined with biofeedback electrical stimulation for stress urinary incontinence in women.MethodsDatabases including CNKI, WanFang, VIP, PubMed, Cochrane Library, Embase, and Web of Science were searched to collect randomized controlled trials (RCTs) on acupuncture combined with biofeedback electrical stimulation for female stress urinary incontinence from database inception to June 1, 2025, and performed a meta-analysis using Stata 15 software.ResultsA total of 33 studies involving 2,860 patients were included in the analysis. Meta-analysis revealed that compared with the biofeedback electrical stimulation group, the acupuncture plus biofeedback electrical stimulation group significantly reduced the number of leakage episodes [SMD = −2.26, 95% CI (−3.42, −1.11)] and urine leakage volume [SMD = −1.79, 95% CI (−2.22, −1.37)], and ICIQ-SF scores [MD = −2.00, 95% CI (−2.61, −1.39)]. Additionally, the acupuncture plus biofeedback electrical stimulation group demonstrated significantly greater increases in pelvic floor muscle strength scores [SMD = 0.99, 95% CI (0.32, 1.65)]. The clinical efficacy of the acupuncture plus biofeedback electrical stimulation group was significantly higher than that of the biofeedback electrical stimulation control group [RR = 1.20, 95% CI (1.16, 1.25)].ConclusionAcupuncture combined with biofeedback electrical stimulation therapy may offer certain advantages in treating female stress urinary incontinence. It may reduce the frequency and volume of urinary leakage, lower ICIQ-SF scores, increase pelvic floor muscle strength scores, and improve quality of life in women.